Bifunctional peptides with antioxidant and angiotensin‐converting enzyme inhibitory activity in vitro from egg white hydrolysates. Issue 9 (29th June 2020) - Zhang, Biying; Liu, Jingbo; Liu, Chang; Liu, Boqun; Yu, Yiding; Zhang, Ting
Abstract: Oxidative stress is frequently associated with hypertension. However, the studies on antihypertensive peptides usually focus on ACE inhibitory activity and ignore antioxidant activity of bioactive peptides. In our research, we optimized enzymatic hydrolysis condition of egg white protein. After that we evaluated both the antioxidant and the ACE‐inhibitory activity in vitro of egg white hydrolysates and its purified fractions. Four peptides, LAPYK, SVIRW, PKSVIRW, and ADWAK, which can match to ovotransferrin were identified from fraction with the highest bioactivity. Among them, LAPYK possessed the strongest activity with ABTS scavenging IC50 of 5.29 ± 0.24 µM, ORAC of 1.50 ± 0.04 µM TE/µM, ACE‐inhibitory IC50 of 12.65 ± 1.34 µM. For further, we explored inhibitory mechanism of LAPYK against ACE. Research on bifunctional peptides is helpful for the application of antihypertensive peptides. Practical applications: At present, the therapeutic drugs for hypertension usually focus on a single target, but the pathogenesis of hypertension is multifactorial, and the combined treatment of multiple targets may have a better therapeutic effect. Compared with commercially available drugs, food‐derived bioactive peptides have lower side effects, as well as exhibit multi‐bioactivities more easily. Exploration of bifunctional peptides with both ACE inhibitory and antioxidant activity provides new ideas for the treatment of hypertension. Abstract : Enzymatic hydrolysis of egg white protein was optimized according to DH. We evaluated both antioxidant and ACE‐inhibitory activity in vitro of egg white hydrolysates and its purified fractions. Four peptides, LAPYK, SVIRW, PKSVIRW, and ADWAK, which can match to ovotransferrin were identified from fraction with the highest bioactivity. LAPYK possessed the strongest bioactivity among of four identified peptides and was confirmed to be a competitive inhibitor against ACE.